ANALISIS MANAJEMEN SUMBER DAYA MANUSIA (MSDM) DALAM UPAYA MENINGKATKAN KINERJA PEGAWAI MELALUI MEKANISME REWARD - Sartono Sartono Sartono; Andri Trianfano Trianfano (Majalah Ilmiah Dinamika Administrasi (MIDA), 2022)
Human resources are one of the important aspects possessed by an agency, both public and private agencies. The management of human resource management is important to do, so this research is intended to analyze and describe the management of human resource management as an effort to improve employee performance, especially employees of the Department of Transportation of Purbalingga Regency through the reward mechanism carried out. This study uses qualitative research methods, with three data collection methods, namely in-depth interviews, observation and documentation. The problems in this study were studied more deeply using 5 (five) factors that affect performance, namely personal factors, work systems, facilities, leadership and situations. The results of this study indicate that the management of human resource management carried out by the Department of Transportation of Puralingga Regency is through a reward mechanism. This mechanism is very important for improving the performance of its employees. However, the facilities and personal factors still need improvement. This is due to the lack of accessibility of supporting facilities for employee performance at the Department of Transportation of Purbalingga Regency.